A política de inclusão na educação profissional: o caso do Instituto Federal de Pernambuco/Campus Recife - Moura, Katia Cristina Bezerra (2013)
Professional training for people with special needs in Brazil started being offered based on school segregation and integration models which contributed very little to the professionalization of students with disabilities. Studies on the professional preparation of students with disabilities have indicated that education for work programs offered by special institutions that organize their actions under such working models do not provide the necessary knowledge for the practice of a profession, nor contribute to professional inclusion as it imposes barriers to full participation of such students in society. 2001 National guidelines for the inclusion of special education in the basic education curriculum state that students with disabilities have the right to vocational training, aiming at promoting a productive integration into society. Accordingly, it recommends that public or private vocational education programs include students with disabilities. In 2008, the policy on inclusive education ensured that the inclusion of students with special needs in vocational education focused on the quality of the programs and determined that professional training institutions must have the support of special education through specialized educational services and other types of support in order to meet the specific educational needs of students with disabilities. In 2011, data from the Resumo Técnico do Censo Escolar da Educação Básica (Technical Summary of the Basic Education School Census) showed that only 0.24 % of special education students included in basic education were enrolled in vocational education programs. Given the national guidelines for the inclusion of special education in the basic education curriculum and the policy on inclusive education that ensures the inclusion of students with disabilities in vocational education, this study aimed to analyze the inclusion policy in this area of education, based on the following aspects: student access to vocational education, services and resources to support student retention and support to include students in the labor market. For this study, qualitative research was the chosen theoretical-methodological approach, and the research strategy used was case study through literature review, observation and semi-structured interview. Oral History Techniques were used to conduct the semi-structured interviews, and interview analysis was conducted using the content analysis method. The research was conducted at a technical and vocational education institution located in the city of Recife, State of Pernambuco. The study included three students with disabilities who graduated from a vocational education program of the researched institution. The testimonials of the interviewed students showed the contradiction between the official content of the inclusion policy and the actual accessibility of the programs as well as the training of the faculty involved.